Research on Type Selection of Submerged Floating Tunnel of Qiongzhou Strait. (2016) - Shengzhong, Wu; Xiang, Chen; Qinxi, Li; Gengren, Cao
Abstract: Based on the analysis of the historical origin and importance of building Qiongzhou Strait Passageway, comparing with construction time in built and super cross-sea engineering under study in the world and comprehensively considering the passenger and cargo flow volume of Hainan Island in future 10 years and 30 years, it is believed that now is the window period of building strait passageway. The paper has used engineering analogy method to make a detailed analysis on the advantages of submerged floating tunnel as fixed cross-sea passageway in nature conservation, construction cost, operation risk and other aspects by comparing with extra-large bridge. Lastly, the paper has discussed the key technology problems in applying submerged floating tunnel to Qiongzhou Strait from crossing way and structure plan, which can serve as reference for this engineering's future construction.